Exposição da audiência aos meios: avanços da abordagem de usos e gratificações - Ferreira, Raquel Marques Carriço (2018)
The approach of Uses and Gratifications has an influential tradition at the audience research dealing with the factors that led the receiver to select and to expose to different media and communication content. The basic assumption of this proposition is that, through the experiences and reflections of the audience on the media contents, they relate which materials are rewarding or useful. Certainly, the model of U&G expanded so much that we do not talk about a theory of U&G anymore, but, in a multi theory scheme. This article aims to introduce the “state of art” of this important reference, pointing its main formulations evident by the use of literature review and the results of a bibliometric research.